2022
DOI: 10.1210/clinem/dgac272
|View full text |Cite
|
Sign up to set email alerts
|

Intrafollicular Concentrations of the Oocyte-secreted Factors GDF9 and BMP15 Vary Inversely in Polycystic Ovaries

Abstract: Context The oocyte-secreted factors GDF9 and BMP15 play essential roles in follicle development and oocyte maturation, and aberrant regulation might contribute to the pathogenesis of PCOS. Objective Are there measurable differences in concentrations of GDF9, BMP15, and the GDF9/BMP15 heterodimer in small antral follicle fluids from women with and without polycystic ovaries (PCO)? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The concentration of GDF9 in spent media was approximately 10-times higher than BMP15, which corroborates recent measurements by our group in follicular fluid from human small antral follicles [39]. This 10-times excess GDF9 in relation to BMP15 indicates that the vast majority of GDF9 are not bound in a heterodimer complex and may have a role on its own during folliculogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…The concentration of GDF9 in spent media was approximately 10-times higher than BMP15, which corroborates recent measurements by our group in follicular fluid from human small antral follicles [39]. This 10-times excess GDF9 in relation to BMP15 indicates that the vast majority of GDF9 are not bound in a heterodimer complex and may have a role on its own during folliculogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Plasma AMH kinetics were similar over time in grafted groups. The tendency of AMH was the same as GDF9 expression, which is a marker of oocyte development quality [ 67 ]. The H-MSCs + OT group showed higher Prog and lower FSH than the OT group on day 3 and 7.…”
Section: Discussionmentioning
confidence: 99%
“…BMP15 is a well-known paracrine factor secreted by oocytes [ 36 ] and primarily responsible for regulating the secretion of steroid hormones, cell mitosis, and follicle development [ 37 ]. Previous research has demonstrated a negative correlation between intrafollicular concentrations of BMP15 and follicle size [ 38 ]. Studies have revealed that the expression of BMP15 in human ovarian granulosa cells stimulates the production of estrogen [ 39 ].…”
Section: Discussionmentioning
confidence: 99%